Synthese generierter und handgebauter Welten mittels WaveFunctionCollapse - Kevin Hagen (2021)
The aim of this bachelor thesis was to test the WaveFunctionCollapse algorithm with regard to its suitability for the generation of procedural worlds and to highlight its eligibility as a tool for game and level designers. Existing traditional algorithms as well as level design fundamentals were investigated. In addition, a level generator based on WFC was developed. Afterwards, the insights gained at the beginning were used to evaluate the results of the generator and the suitability of the algorithm for the synthesis of generated and handcrafted worlds. It has been shown that the WFC definitely has potential for use in real production. Furthermore, it was found that an implementation of the SimpleTiled Model is better suited than the Overlapping Model. The thesis is aimed at both beginners and advanced students in dealing with the topic of PCG.